ENERGY AND PROTEIN INTAKE IN STUNTING TODDLERS IN THE WORK AREA OF PUBLIC HEALTH CENTER CITY SOUTH REGION, KEDIRI CITY - Laila Adhani, Eka; Rizky Indrasari, Oktovina (Universitas Nahdlatul Ulama Surabaya, 2022)
Stunting is one of the nutritional problems faced in developing countries such as Indonesia. The incidence of stunting is influenced by several factors: the lack of food intake containing energy and protein. The purpose of the study was to determine the description of energy and protein intake in stunting in the UPTD Work Area of ​​the Southern City Health Center, Kediri City. Research descriptive was conducted in four villages, namely Ngronggo, Rejomulyo, Manisrenggo, and Kaliombo. The sample in this study was 10 respondents who were stunted and individual assessment of nutritional intake through a food consumption survey was conducted through the Semiquantitative Food Frequency Questionnaire (SFFQ). The results showed that toddlers aged 2-3 years with energy intake in the category of fewer than 7 toddlers, while toddlers at the age of 4-5 years as many as 3 toddlers with energy intake in the category of less, and the results of the calculation of protein intake found that toddlers aged 2-3 years had the number of protein intake in the sufficient category is 2 toddlers, while the other 5 toddlers have an adequate protein intake in the less category. Meanwhile, toddlers aged 4-5 years have protein intake in the less category because they have not met the protein adequacy rate (RDA) of (25 grams). Energy intake in stunting aged 2-3 years is said to be lacking and has not met energy intake, while toddlers aged 4-5 years have not met energy intake and protein intake in toddlers aged 2-3 years there are 2 stunting who have adequate protein intake while toddlers age 4-5 years has not met the intake of protein.